EFFECT OF CHANGE OF COASTAL ZONE DEPTH ON SPECTRUM OF IRREGULAR WAVES - Городецька, Наталія Сергіївна; Щербак, Тетяна Миколаївна; Нікішов, Володимир Іванович (Science-based technologies, 2016)
Transformation of the irregular wave spectrum on inhomogenety of bottom surface that is characterized by a sharp change of depth is studied. The normal incidence of waves is considered. The superposition of two TMA spectra, in which the finite depth of fluid is taken into account, with different frequencies of spectral maxima corresponding to surface waves and swell is used as the unidirectional spectrum model of waves. Following RDT (Rapid Distortion Theory) approach, the linear theory for investigating of the spectrum transformation under action of abrupt change of the depth is applied. It is assumed that the modification of spectral components is caused by abrupt change of depth, and nonlinear effects of their interaction are manifested at some distance from the considered region. The expansion of sotution into a series of eigenfunctions is used to solve the boundary-value problem of wave transformation. The dependence of coefficient of transmission of waves over abrupt change of depth on the wave number of incident wave is obtained on the base of the improve reduction method. The features of transformed spectrum for different parameters of the problem are analized. It is shown that spectral amplitudes grow after step and corresponding wave lengths decrease, that is, waves become more steep and can be broken down..